Design and Development of Pneumatic Coconut Cutter Using DFMA Approach - Mohamad Norfadzlan Kamarudin,; Mohd Amri Lajis, (Progress in Engineering Application and Technology, 2024)
This research study examines a pneumatic coconut cutter machine that utilises Design for Manufacture and Assembly (DFMA) methodologies. DFMA, which encompasses Design for Manufacturing (DFM) and Design for Assembly (DFA), is employed to reengineer a preexisting product with the objective of minimising expenses, time, and components. The objective of the study is to improve the efficiency of design and the accuracy of cost estimation for a pneumatic coconut cutting machine, in order to make it more effective. The present product is remodelled and a new design, called pneumatic coconut cutter v2, is proposed using SolidWorks 2022 software. The DFA manual handling worksheet is utilised to compute the duration of manual assembly, demonstrating an enhancement in design efficiency from 26.8% to 40.23%. The cost assessment shows that the pneumatic coconut cutter v2 is cheaper, with a price of RM359.06, compared to the original design, which costs RM528.22. The study confirms the efficacy of DFMA in attaining enhanced product results, providing prospective advantages to the machine manufacturing industry by developing a cost-efficient pneumatic coconut cutter without sacrificing functionality